Release of sunflower seed dormancy by cyanide cross-talk with ethylene signalling pathway - Oracz, Krystyna (Journal of experimental botany, 2008)
Freshly harvested sunflower (Helianthus annuus L.) seeds are considered to be dormant because they fail to germinate at relatively low temperatures (10 degrees C). This dormancy results mainly from an embryo dormancy and disappears during dry storage. Although endogenous ethylene is known to be involved in sunflower seed alleviation of dormancy, little attention had been paid to the possible role of cyanide, which is produced by the conversion of 1-aminocyclopropane 1-carboxylic acid to ethylene, in this process. The aims of this work were to investigate whether exogenous cyanide could improve the germination of dormant sunflower seeds and to elucidate its putative mechanisms of action. Naked dormant seeds became able to germinate at 10 degrees C when they were incubated in the presence of 1 mM gaseous cyanide. Other respiratory inhibitors showed that this effect did not result from an activation of the pentose phosphate pathway or the cyanide-insensitive pathway. Cyanide stimulated germination of dormant seeds in the presence of inhibitors of ethylene biosynthesis, but its improving effect required functional ethylene receptors. It did not significantly affect ethylene production and the expression of genes involved in ethylene biosynthesis or in the first steps of ethylene signalling pathway. However, the expression of the transcription factor Ethylene Response Factor 1 (ERF1) was markedly stimulated in the presence of gaseous cyanide. It is proposed that the mode of action of cyanide in sunflower seed dormancy alleviation does not involve ethylene production and that ERF1 is a common component of the ethylene and cyanide signalling pathways